Antagonismo do receptor da adenosina A2a : nova perspectiva para o tratamento da doença de Parkinson - Aguiar, Lissiana Magna Vasconcelos (2009)
Parkinson disease (PD) is a neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra pars compacta. Antagonists of the A2A subtype of adenosine receptor have emerged as a target for nondopaminergic antiparkinsonian agents. The present work showed the effects of caffeine and 8-(-3-chlorostyryl)-caffeine (CSC), A2A receptors antagonists, on behavior and biochemical alterations in 6-OHDA-lesioned rats, as a model of PD. Animals (male Wistar rats, 260-280 g) were injected daily with caffeine (10 and 20 mg/kg,i.p., 1h after 6-OHDA lesion for 14 days or six days after 6-OHDA lesion for 7 days), or CSC (1 and 5 mg/kg, i.p., 1h after 6-OHDA lesion for 7 days) alone or associated with L-DOPA (CSC 1 mg/kg, i.p. + L-DOPA 50mg/kg + Benzerazida 12,5 mg/kg, i.p., six days after 6-OHDA lesion for 7 days). Fourteen days after 6-OHDA, the animals’ behavior was assessed by monitoring body rotations induced by apomorphine (3 mg/kg, i.p.). The results showed that the drastic increase in body rotation, induced by the 6-OHDA lesion, after the apomorphine challenge, was significantly (50 times) and dose-dependently reversed by CSC or caffeine. The decreased striatal levels of DA and metabolites, in the 6-OHDA-lesioned rats (75-85%), were blocked after caffeine or CSC alone or in association with L-DOPA treatment as well as the concentrations of NE, 5-HT and 5-HIAA. These effects were potentiated in 6-OHDA-lesioned animals treated with the association of CSC and L-DOPA. Concentrations of the amino acids glutamate and GABA were significantly increased (3.8 and 3 times, respectively) in the 6-OHDA-lesioned rat striatum. Similarly, CSC also reversed these alterations significantly. We also demonstrated protective effects against 6-OHDA-induced cytotoxicity in rat mesencephalic cells. Caffeine or CSC significantly increased the number of viable cells after their exposure to 6-OHDA, as measured by the MTT assay. While nitrite levels and lipid peroxidation in the cells were drastically increased by 6-OHDA, its concentration was brought toward normality after caffeine or CSC. 6-OHDA decreased the number of normal cells while increasing the number of apoptotic cells. Caffeine or CSC, significantly recovered the number of viable cells, and decreased the number of apoptotic cells, as compared to the group treated with 6-OHDA alone. Interestingly, while a significant lower number of activated microglia was seen after cells exposure to caffeine plus 6-OHDA, this was not the case after cells exposure to CSC plus 6-OHDA. While caffeine lowered the percentage of reactive astrocytes increased by 6-OHDA, CSC showed not effect. These results showed a strong neuroptrotection afforded by caffeine or CSC on rat mesencephalic cells exposed to 6-OHDA. In conclusion, we showed that CSC or caffeine reversed behavior and biochemical alterations, observed in the 6-OHDA-lesioned rats, pointing out to the potential benefit of A2A receptors antagonists as non-dopaminergic therapeutic targets for the treatment of PD.